Simplified procedures to treat periodontal intraosseous defects in esthetic areas. Issue 1 (1st March 2018) - Trombelli, Leonardo; Simonelli, Anna; Minenna, Luigi; Vecchiatini, Renata; Farina, Roberto
Abstract: Successful treatment of deep intraosseous defects in esthetic areas implies clinical improvement of the lesion consistent with long‐term tooth survival as well as the preservation (or improvement) of esthetics. It is hoped that such treatment end points may be reached through procedures (which we have termed as 'simplified') that, on the one hand can be easily and successfully applied by the majority of clinicians, and, on the other hand, are well tolerated by patients in terms of postsurgical pain and discomfort, adverse events and cost. In this review, we describe the technical aspects of the simplified procedures currently available (i.e. nonsurgical therapy and the single flap approach and its variants). Also, we analyze the effect of such procedures on clinical parameters and patient‐centered outcomes. While nonsurgical therapy seems to be appropriate per se in lesions with a probing depth of < 7 mm and a limited intraosseous component, severe intraosseous defects can be successfully treated using simplified surgical procedures. Overall, data support the effectiveness of simplified surgical procedures and indicate that they result in minimal esthetic impairment (i.e. post‐treatment recession) and a more tolerable postoperative course when compared with conventional surgical (double flap) approaches. In particular, the single flap approach was shown to be at least as effective as traditional papilla‐preservation techniques when evaluated either as a stand‐alone protocol or in combination with regenerative devices. Bioactive agents have shown the most appropriate regenerative technology when used in association with simplified surgical procedures.